10d+6-6d=22

Simple and best practice solution for 10d+6-6d=22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10d+6-6d=22 equation:


Simplifying
10d + 6 + -6d = 22

Reorder the terms:
6 + 10d + -6d = 22

Combine like terms: 10d + -6d = 4d
6 + 4d = 22

Solving
6 + 4d = 22

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 4d = 22 + -6

Combine like terms: 6 + -6 = 0
0 + 4d = 22 + -6
4d = 22 + -6

Combine like terms: 22 + -6 = 16
4d = 16

Divide each side by '4'.
d = 4

Simplifying
d = 4

See similar equations:

| -3(x+8)=-15 | | -5(2.5+x)=10 | | -9x^2+120x-12=0 | | -1(-3x-5)=-7 | | 0.7+y=-1.63 | | 125m-100m+43650=45225-200m | | 6/5=2/5x | | 3=-3(4x+6) | | y=(x^3-6x^2-x+6)(x^2-2x+5) | | 6/-16 | | 3x-12=4x+2-x | | 2x-4=-x-5 | | e^5x=26 | | 5[x-6]+2=7x-6 | | 7c+2=31 | | -2x-12=-6(2+6n) | | y=(x-6)(x^2-1) | | 3(2x-5)-6(2x-6)= | | 1/2×-3=11 | | (3a-1)+(2a+1)+(5a-2)=28 | | 4d-45d=-8 | | 4(-7x+8)=3x+32 | | 36/60=x/100 | | -5x+5=2x-16 | | 3a-1=x | | 77.50=0.15x+10 | | x^2-.2x+0.05=0 | | -1-n=-4(3n+3) | | 5x+12-x=12+4x | | 36/200 | | Y-9=(11/4)x-2 | | 3c-5=2c+50 |

Equations solver categories